Role of Biological Response Modifiers in the Treatment of Rheumatoid Arthritis-A Review (TAJ: Journal of Teachers Association, 2009)
Rheumatoid arthritis is a chronic disease with the potential to cause substantial joint damage and disability. During the past 10 years, improved understanding of the pathophysiology of rheumatoid arthritis has led to several key changes in the approach to therapy. Most important of that is the development of some biological agents interfering with the activity of several important cytokines. Infliximab, etanarcept, and adalimumab are TNF blockers, anakinra is IL-1 receptor antagonist, and rituximab is anti CD-20 monoclonal antibody. These newer agents proved to be useful for alleviating symptoms and slowing the disease progression in the patients with RA who have failed to respond to conventional DMARDs.   doi: 10.3329/taj.v17i1.3494 TAJ 2004; 17(1) : 71-76